FUTURE EDUCATOR TRAINING IN PRESCHOOL CHILDREN’S ENVIRONMENTAL COMPETENCE FORMATION - Карапузова, Ірина; Коваль, Віта (Modern engineering and innovative technologies, 2022)
The article analyzes the peculiarities of the organization of professional future teacher training in the formation of preschoolers’ environmental competence in the process of familiarizing them with nature at Poltava V. G. Korolenko National Pedagogical